Antibiotic prescribing practices in the presence of extended-spectrum β-lactamase (ESBL) positive organisms in an adult intensive care unit in South Africa – A pilot study. Issue 4 (1st December 2018) - Fourie, T.; Schellack, N.; Bronkhorst, E.; Coetzee, J.; Godman, B.
Abstract: Introduction: Antimicrobial resistance is one of the most severe health threats globally. Extended spectrum β-lactamases (ESBLs) are enzymes produced by a variety of gram-negative bacteria, which lead to an increase in resistance to commonly used antibiotics and are associated with higher morbidity and mortality. Objectives: Assess the prescribing practices prior to, and after, positive ESBL producing microbiology cultures in an adult ICU setting, according to sensitivity reports obtained from the clinical laboratories from January 2013 until January 2014. Subsequently use the findings to guide future practice. Method: Retrospective study at a private hospital in Pretoria, Gauteng Province. All adult patients older than 18 years of age that were admitted to either the MICU (multi-intensive care unit) or the TICU (trauma intensive care unit) with a positive producing ESBL culture during their hospitalised stay were assessed. Results: During the study period, 39 patients in the MICU and TICU had positive ESBL microbiology results. The majority of positive ESBL results were due to Klebsiella pneumonia isolates. Antibiotics prescribed post ESBL positive culture were appropriate according to the sensitivity report in 64% of patients. 22 patients survived and 17 patients died. All the patients that died were on invasive ventilatory support. Conclusion: Clinically it appears as if patients who received appropriate therapy according to the microbiology results showed a better clinical outcome than those with inappropriate therapy. This underlines the importance of appropriate prescribing practices in combination with co-morbid conditions. Invasive ventilatory support can be identified as a clear risk for contracting an infection due to an ESBL producing organism.